Programming Parameters and Techniques in Trigeminal Ganglion Stimulation for Intractable Facial Pain. Issue 6 (3rd November 2020) - Gupta, Kunal; Texakalidis, Pavlos; Boulis, Nicholas M.
ABSTRACT: Objectives: Atypical facial pain syndromes are challenging disorders to manage and often incur limited benefit with surgery for classical trigeminal neuralgia presentations, such as microvascular decompression or ablative procedures. Neurostimulation of the trigeminal ganglion and peripheral nerves can be effective at treating atypical presentations of trigeminal facial pain affecting the V1‐3 dermatomes, and the surgical techniques are well described. The stimulation parameters, however, have thus far received limited description; we therefore sought to describe programming strategies. Materials and Methods: We performed a retrospective chart review, examining patients that underwent trigeminal ganglion stimulation (TGS) and nerve branch stimulation for atypical facial pain and trigeminal neuropathic pain, and describe the programming strategies in detail. Results: We describe the use of high‐frequency stimulation (1000 Hz), with alteration in pulse width (60–220 msec) and amplitude (0.5–3 V) to achieve effective treatment of refractory trigeminal facial pain. These parameters differ from existing published parameters for trigeminal nerve branch stimulation. We also describe the programming of specific contacts on each lead to target specific aspects of the individual patients' facial pain. Conclusions: The use of effective programming strategies is critical to the success of neurostimulation surgical treatments; however, the critical details in programming strategies typically receive limited description. We report on the use of several successful programming strategies for TGS, to assist pain providers in successfully applying these surgical techniques in these difficult to manage atypical facial pain syndromes.